KUALITAS PELAYANAN PENANGANAN PENGADUAN IZIN MENDIRIKAN BANGUNAN PADA BADAN PELAYANAN PERIZINAN TERPADU KOTA PALU - Azir, Mohamad (Katalogis, 2015)
This research to know how the quality service handle of permission accuratuins cause stand up buildings to permission service body compact. Kind of appraisal that using are observation,interview,documentation, and triangulasi. The drawing technic informan using appraisal analist model qualitative. The theory that using is theory from Zethmal, Parasuraman and Berry, consist of five demention af are:tangibles,reliability,responsiveness,assurance and emphatyr.Â Based on research that do it the quality service handle of permission accurations cause stand up buildingâ€™s to permission service body compact. Is not maximal.First;Tangibles dimention is medium and infrastructure is not appropriate like less white waiting room and chair also is not appropriate with aplicate quantytas althought with public toilet. Second ; Realibility dimentionis appliance speed to give accurations service is not appropriate with hopeless society,because remedial of arbitrariness accurations there is in technic official. Third ; Responsiveness dimentoin is official respond to receiveapplicate complint is very good ,but the speed to finish accurations is not maximal. Fourth ; Assurance dimention is quarantee that given by official to aplicate is not on time, because less official respons hire of performar technic society accuration. Fifth ; Emphaty dimention is Accurationservice that official given not discriminatife and official always give respect full well manered oservice.